2010
DOI: 10.1007/s10493-010-9403-7
|View full text |Cite
|
Sign up to set email alerts
|

Tick infestation (Acari: Ixodidae) in roe deer (Capreolus capreolus) from northwestern Spain: population dynamics and risk stratification

Abstract: During the 2007 and 2008 hunting seasons (April-October) the skin of 367 roe deer (Capreolus capreolus L.), hunted in different preserves from Galicia (Northwestern Spain), were examined for ticks (Acari: Ixodidae). The overall prevalence of infestation by ticks was 83.1%. The predominant species was Ixodes ricinus (83.1%), whereas a single Dermacentor marginatus specimen appeared in one roe deer. All developmental stages of I. ricinus were found parasitizing roe deer, the adults being the most frequent (82.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
6
16
0
2
Order By: Relevance
“…In total, 8885 ticks were collected; all developmental stages of I. ricinus were found infesting roe deer, with adult females being the most frequent, followed by nymphs, males and larvae (Table 1); these differences were significant by a Kruskal-Wallis test ( 2 = 87 145; P < 0.001). Our results corroborate those of Vázquez et al (2011) and Pato et al (2013), who found that, in addition to adults, deer could also support a high proportion of immature stages. The median number of ticks infesting roe deer was similar in both areas (Table 1) and the differences were not significant using the Kruskal-Wallis test (P > 0.05).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In total, 8885 ticks were collected; all developmental stages of I. ricinus were found infesting roe deer, with adult females being the most frequent, followed by nymphs, males and larvae (Table 1); these differences were significant by a Kruskal-Wallis test ( 2 = 87 145; P < 0.001). Our results corroborate those of Vázquez et al (2011) and Pato et al (2013), who found that, in addition to adults, deer could also support a high proportion of immature stages. The median number of ticks infesting roe deer was similar in both areas (Table 1) and the differences were not significant using the Kruskal-Wallis test (P > 0.05).…”
Section: Resultssupporting
confidence: 91%
“…Our results corroborate those of Vázquez et al . () and Pato et al . (), who found that, in addition to adults, deer could also support a high proportion of immature stages.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Wild ruminants such as WTD and roe deer are among the major feeding hosts for ticks in the Eastern US and Europe, respectively, and thus considered to contribute to a rapid increase in the population of ticks (Spielman et al, 1985; Vázquez et al, 2011; Medlock et al, 2013). WTD is considered one of the major reservoir hosts for an apathogenic variant (Ap-V1) of A. phagocytophilum in the Eastern US (Massung et al, 2005).…”
Section: Hosts and Reservoirsmentioning
confidence: 99%